A review on efficiency improvement methods in organic Rankine cycle system: an exergy approach - Gollangi Raju; Nagamalleswara Rao Kanidarapu (International Journal of Advances in Applied Sciences, 2022)
Exergy, one of the handed-down energy conservation techniques, which can obtain from thermodynamic laws (first and second), will disclose the work presented within the system, the amount of irreversibility as well as what are the possible ways to reduce inefficiencies in the system. This discourse mainly highlighted various techniques and possible methods for efficiency improvement in the organic Rankine cycle (ORC). That means mainly concentrated on following key parameters like the selection of working fluid, suitable expander, the different heat sources of an evaporator, and modifications in heat exchanger based on the application of ORC system through an exergy approach for better performance, decrease energy losses, and destruction rate. This review can help to pontificate for better-summarized results that were done before and suggest some ideas for how to select an optimized parameter for better efficiency and to decrease the destruction rate in the ORC system.